Michigan Railroads & Railroad Companies - Meints, Graydon M. (Book collections on Project MUSE., 1992)
Michigan Railroads and Railroad Companies is an invaluable reference manual for everyone interested in regional transportation history, the history of railroading, and Michigan history in general. It contains complete, cross-referenced listings for every company formed to operate a railroad in the state of Michigan. In addition to the comprehensive entries for major lines, Graydon Meints has included details about the many small, common-carrier steam and electric companies, logging roads, and numerous other primitive and contemporary rail systems. This encyclopedic reference.